2016
DOI: 10.1080/19425120.2016.1243599
|View full text |Cite
|
Sign up to set email alerts
|

Annual Spawning Migrations of Adult Atlantic Sturgeon in the Altamaha River, Georgia

Abstract: The Atlantic Sturgeon Acipenser oxyrinchus has declined throughout its range, and the species is now protected under the U.S. Endangered Species Act. Information on the timing and extent of spawning migrations is essential for the development and implementation of effective management and recovery strategies, yet this information is lacking for most populations. The objectives of this study were to document and identify temporal and spatial patterns in the seasonal movements and spawning migrations of Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Across all three rivers in this study, 30.4% of tagged Atlantic Sturgeon were detected outside of their natal river after completing their transition to the MMJ stage during the winter after tagging (Table ). Given that Ingram and Peterson () found that spawning occurs from October to December in the Altamaha River, the results of this study suggest that RRJs began their initial transition to MMJs during the winter and early spring months immediately after reaching age 2. In all three study rivers, age‐1 RRJs dispersed downstream in their natal estuary during the winter.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Across all three rivers in this study, 30.4% of tagged Atlantic Sturgeon were detected outside of their natal river after completing their transition to the MMJ stage during the winter after tagging (Table ). Given that Ingram and Peterson () found that spawning occurs from October to December in the Altamaha River, the results of this study suggest that RRJs began their initial transition to MMJs during the winter and early spring months immediately after reaching age 2. In all three study rivers, age‐1 RRJs dispersed downstream in their natal estuary during the winter.…”
Section: Discussionmentioning
confidence: 48%
“…Because tagged fish are only detected when they come within range of a receiver, it is not possible to ascertain whether an individual's lack of detections indicates mortality. Based on recaptures of transmittered fish in this and other studies from our research group (Ingram and Peterson ), surgical incisions healed completely within 1 month of capture. Of the 92 total fish tagged across 3 years in this study, 15 (16.3%) were last detected less than 1 month after being tagged.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…; Kahn et al. ; Ingram and Peterson ); therefore, only fish measured to be greater than or equal to this length were considered ATS. We also observed shadows created by marks in the sonar and looked for determining features of ATS (i.e., heterocercal tail, dorsal fin), but when estimating length for each sturgeon we measured the actual mark created by the sonar rather than the shadow produced by the mark (Flowers and Hightower , ).…”
Section: Methodsmentioning
confidence: 99%
“…In northern populations, spawning occurs in the spring (Bain, 1997), whereas the results of recent studies indicate that at least some central and southern populations spawn in the fall (Hager et al, 2014;Smith et al, 2015;Ingram and Peterson, 2016). During the first several years of life, the young fish, known as river-resident juveniles (RRJs), occupy estuarine habitats near the freshwater-saltwater interface.…”
mentioning
confidence: 99%